Developing a resilient Crisis Management Plan (CMP) for the Malaysian construction sector / Anis Mardhiah Mukhtar ... [et al.] - Mukhtar, Anis Mardhiah; Mohd Nordin, Rumaizah; Hashim, Norfashiha; Abas, Abdul Aziz (UiTM Press, 2022)
Construction is a diverse and complex sector. It consists of projects with intricate activities and interfaces between stakeholders who undergo a series of development phases using numerous resources, integration of technologies, materials, and approaches. Theoretically, construction projects can be well planned. However, it is being exposed to unanticipated events or crises that could disrupt original plans, affecting organizations' operation and progress of construction projects. Problems may even have the propensity to destroy the organization significantly. Considering the current paradigm of crisis, the Covid-19 outbreak that emerged in late 2019 has continuously left a lasting impact on the construction industry. As of August 2020, Covid-19 has spread to over 200 countries, and the number has increased beyond 100,000 cases in Malaysia. Regardless of Covid-19 has placed great stress on all aspects worldwide, it led to the closure of most construction businesses, causing contraction towards industry growth to the greatest to extend of -7.9%, the lowest since 1999. In this context, the effort to ensure the preparedness of the construction organizations against crisis has become an issue. Hence, this paper aims to structure a framework that consists of principles and processes which can recover and develop a resilient construction industry. The method used for this study is Systematic Literature Review of related journals gathered through WOS, ScienceDirect, and Google Scholar, reports, and relevant references from Government Authorised agencies circa 1998 to 2020. 4262 articles were identified, and 111 papers were subsequently selected for further analysis. Based on the findings, there are five major phases of CM, including prepare, prevent, respond, evaluate, and redesign. The proposed CM includes 4 elements and 2 outputs. The preliminary findings form the foundation for an extended investigation to offer a specific crisis management plan to guide the Malaysian construction industry, specifically in Klang Valley, to be resilient during plight.